2015
DOI: 10.1111/jeb.12615
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and reproduction: antioxidant supplementation alleviates telomere loss in wild birds

Abstract: Reproduction is inherently costly. Environmental stressors, such as infection and limited food resources, can compromise investment at each breeding attempt. For example, recent data on captive birds showed that increased reproductive effort accelerates ageing. However, the effects of nutritional status and infection on ageing remain unknown. Telomeres function as protective caps at the ends of eukaryotic chromosomes, and changes in telomere length is a commonly used proxy for ageing. To partially address the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 72 publications
3
54
0
2
Order By: Relevance
“…Although extra‐pair copulations occur before the nestling provisioning phase and therefore are unlikely to be affected by an experimental treatment to adult birds during this phase, we confirmed that the experiments in 2012 (Badás et al. ) and 2013 (unpubl. data) were not related to extra‐pair paternity (2012: χ 2 3 = 2.64, P ‐value = 0.45, N = 78; 2013: χ 2 2 = 2.29, P ‐value = 0.32, N = 63).…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…Although extra‐pair copulations occur before the nestling provisioning phase and therefore are unlikely to be affected by an experimental treatment to adult birds during this phase, we confirmed that the experiments in 2012 (Badás et al. ) and 2013 (unpubl. data) were not related to extra‐pair paternity (2012: χ 2 3 = 2.64, P ‐value = 0.45, N = 78; 2013: χ 2 2 = 2.29, P ‐value = 0.32, N = 63).…”
Section: Methodssupporting
confidence: 85%
“…In season 1, reproductive success could not be evaluated because this was affected by an experimental treatment (Badás et al. ). For each season and response variable, to avoid multicollinearity or sample size problems when a large number of explanatory variables are evaluated, we designed partial least squares regression models (PLSR; Carrascal et al.…”
Section: Methodsmentioning
confidence: 99%
“…These results combined suggest that availability of egg maternal and dietary VE has little influence on telomere dynamics in early life stages. However, such effects may become apparent at a later life stage, as shown for blue tit nestlings where the positive effect of a one-shot treatment with VE and methionine via subcutaneous injection on TL could be recorded 1 year after treatment [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have examined the effects of within‐brood competition on telomere shortening (Boonekamp et al., ; Nettle et al., ; Reichert et al., ; Voillemot et al., ) or the role of oxidative stress on telomere dynamics by manipulating antioxidants (Badás et al., ; Kim & Velando, ; Noguera, Metcalfe, Boner, & Monaghan, ) or corticosterone (Haussmann, Longenecker, Marchetto, Juliano, & Bowden, ) during development. In this study, we experimentally manipulated developmental stress by means of a brood size manipulation to assess its effect in telomere length in a wild passerine, the spotless starling, Sturnus unicolor .…”
Section: Introductionmentioning
confidence: 99%